2002
DOI: 10.1002/j.2161-1920.2002.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting self‐esteem during unemployment: The effect of gender, financial deprivation, alternate roles, and social support

Abstract: Two hundred and one unemployed men and women participated in a crosssectional study that assessed self-esteem, financial deprivation, number of alternate roles, and use of social support. Financial deprivation, alternate roles, and social support each had a main effect on self-esteem. In addition, these variables interacted with gender to affect self-esteem. Specifically, financial deprivation had a greater negative association with self-esteem in men as compared with women. In contrast, alternate roles and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 58 publications
(56 reference statements)
4
53
2
9
Order By: Relevance
“…While speculative, these arguments are also consistent with empirical studies documenting that the mental distress experienced by displaced workers is generally more severe for men than women (McKee-Ryan et al 2005, Grzywacz and Dooley 2003, Waters and Moore 2002.…”
Section: Effect Of Mothers' Plant Closuresupporting
confidence: 70%
“…While speculative, these arguments are also consistent with empirical studies documenting that the mental distress experienced by displaced workers is generally more severe for men than women (McKee-Ryan et al 2005, Grzywacz and Dooley 2003, Waters and Moore 2002.…”
Section: Effect Of Mothers' Plant Closuresupporting
confidence: 70%
“…As mentioned earlier, one of the most important protective factors from the negative consequences of unemployment is social support (Roberts et al 1997;Waters & Moore 2002, Axelsson & Ejlertsson 2002, Bjarnason & Sigurdardottir 2004. As unemployed individuals in our research did not differ in number of friends or feelings of loneliness from the employed and students, it can be assumed that their social support is good enough to protect their health.…”
Section: Discussionsupporting
confidence: 54%
“…In this study on health consequences of unemployment we paid attention to the gender of respondents. Among adults, there is more or less consistent evidence that females cope with unemployment better than males, and the negative effect of job loss on their health is not so strong as among males (Waters & Moore, 2002;Artazcoz et al 2004). However, this fi nding seems not to be confi rmed among youth, either in the present or in any other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of unemployment among females is artificially reduced by household work or maternity and parental leave, which lasts for three years in the Slovak Republic. Furthermore, it has been found that females experience their unemployment less negatively than males, which could lead to lower mortality rates 3,10,25,27,29 . These could be the reasons why the overall influence of female unemployment on their mortality is reduced.…”
Section: Discussionmentioning
confidence: 99%